Instant Re-Implantation of Avulsed Teeth - Smita Paul; Sambarta Das; Nirmal Debbarma; Barun Dasgupta; Bidyut Seal; Ayesha Satapathy (Journal of Pharmacy and Bioallied Sciences)
Successful re-plantation of avulsed tooth in children demands instantaneous management. This case report emphasizes the efficient treatment of a 09-Year-old boy who suffered an avulsion of the maxillary right central incisor at his school. The patient reported within half an hour of the traumatic dental injury with the avulsed tooth in his hand wrapped in a piece of newspaper. Immediately the tooth was placed in normal saline (0.7%) when the patient arrived and conventional Root Canal Therapy (RCT) was done extra-orally. After the root canal, the tooth was re-planted according to the IADT guidelines and stabilized in place with splinting. Our interpretation suggests that re-plantation of an avulsed tooth as quickly as possible, using appropriate splint and planned root canal therapy, promotes faster periapical healing and yields a better prognosis.